Essay on gardens : a chapter in the French picturesque translated into English for the first time - Watelet, Claude-Henri (Penn studies in landscape architecture, 2003)
The result is a horticultural and ecological laboratory that includes a residence, a farm, stables, a dairy, an apiary, a mill, walks, vistas, flower beds, an area reserved for medicinal plants, decorative statues, a medical laboratory, and even a small infirmary for ailing members of the community." "Given the wide scholarly interest in the field of garden design and its history, this first English edition of Watelet's small but influential book will interest historians of landscape design as well as students of the history of architecture."--Jacket